PENINGKATAN KEMAMPUAN MENULIS TEKS CERITA SEJARAH DENGAN MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES SISWA KELAS XII SMKN 1 PURWOJATI - Purwahono (Jurnal Tawadhu, 2022)
This research is a classroom action research. The purpose of this study is to improve the ability to write historical narrative texts with an example non example learning model for class XII students of SMK Negeri 1 Purwojati, Banyumas Regency. The indicator of the success of this research data is if there is an increase in students' learning mastery based on the minimum completeness criteria (KKM) for Indonesian Language and Literature subjects at SMK Negeri Purwojati, Banyumas Regency, with a value of 70. The conclusion of this study is the use of the model example non example learning can improve the ability to write historical narrative texts for class XII students of SMK Negeri Purwojati, Banyumas Regency, Central Java Province.